PROPERTI MEKANIK BETON RINGAN DENGAN MENGGUNAKAN AGREGAT BATU APUNG SERTA ABU TERBANG SEBAGAI PENGGANTI SEBAGIAN SEMEN PORTLAND DAN SUPERPLASTICIZER - I Gusti Agung Neny Purnawirati; I M. Alit K. Salain; Dharma Putra (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2016)
Abstract Researches about lightweight concrete that be held nowadays, have some weakness particularly in compressive strength. Usually researches about lightweight concrete with pumice that uses Portland giving result about 13,5-16,8 MPa of compressive strength. For reducing the cement using, it is needed to find an alternative of Portland cement exchanged that improve the compressive strength at once. In addition, for compressive strength increasing it is needed to use water low water stirring. But, with a low water stirring, so mixing will be difficult for doing so it is needed superplastizer for mixing easier. Fly ash varieties as an exchanged of a part of Portland cement start from 0%, 10%, 20%, 30%, 40%. The weight ratio of cement : sand : pumice is 1,00 : 3,07 : 1,14 with factor adhesive water 0,32 refers SNI 03-3449-2002 with compressive strength of the plan is 18 MPa. This study uses superplasticizer 0,4% and 0,8% of cement weight is added during the mixing concrete. Distribution of sand and pumice designed by SNI 03-2834-2000, zone 1 for sand and graduation maximum diameter of 12,5 for pumice. Increase compressive strength and modulus of elasticity occurred with age concrete hydration of 28 days to 56 days. Compressive strength increase with fly ash varieties as an exchanged of a part of Portland cement with fly ash until 20% and then decreasing. However, the replacement of Portland cement 40% with fly ash was produced higher compressive strength than without fly ash. A relatively same indicator be shown on modulus of elasticity that be carried out from changing of 20% Portland cement by fly ash and 40% superplasticizer consecutively as 14,34 MPa and 10766,71 MPa in 28 days and 18,12 MPa and 11006,56 MPa in 56 days.